Faktor-Faktor yang Mempengaruhi Kecemasan Mahasiswa dalam Menghadapi Tugas Akhir - Ramadhan Trybahari Sugiharno; Wibowo Hanafi Ari Susanto; Frengki Wospakrik (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to look at the factors that influence students in facing their final project. This research method is quantitative research with a cross-sectional study design. The results showed that the average age of the respondents was 21 years, with the youngest 20 years old and the oldest 22 years old. Most (76.3%) of the research respondents were 45, and of the total respondents, the majority (64.9%) of 24 respondents experienced moderate anxiety. And 31 respondents (83.8%) have high family support then, strong peer influence is 31 respondents (83.8%), the influence of supervisors is vital to as many as 33 respondents (89.2%), and the influence of the environment good as many as 30 respondents (81.1%). The bivariate analysis results showed that the p-values ​​for all variables were < 0.05. In conclusion, there is a significant relationship between support from family, peers, supervisors, and the environment with student anxiety in facing the final project. Keywords: Student, Anxiety, Nursing, Final Project